Pengaruh Penggunaan Strategi Pembelajaran Type Card Sort Terhadap Pemahaman Peserta Didik Pada Materi Makna Hubungan Simbol Sila-Sila Pancasila - Zahraya, Loeti Siti; Hidayat, Rahmat; Hidayati, Eva Fauzia Sri (Journal of Elementary Education: Strategies, Innovations, Curriculum, and Assesment, 2024)
Pancasila and civics is a subject that plays an important role in translating the values of Pancasila into students' daily attitudes and behaviors. This study aims to see the effect of Card Sort Learning Strategy and Expository Learning Strategy on the learning process of the meaning of the relationship between the symbols of Pancasila commandments in civics learning subjects for students in elementary schools. This study used a quantitative approach, type of research True Experimental, with Pretest Posttest Control Group Design. The study was conducted at 7 Ciamis State Elementary School, with a population of 88 subjects and a sample of 30 subjects from grade IV A drawn by the technique of simple random sampling. The research instrument used a test in the form of multiple choice questions as many as 20 items. Data analysis was done by descriptive analysis and inferential analysis using t-test. The instrument in the form of a test before (pre-test) applied to the Type Card Sort learning strategy achieved an average score of 52.67 with a sufficient value category, while the average score after treatment (post-test) on the Type Card Sort learning strategy was 94.47 with a very high value category. The inferential statistical analysis shows t count = 6.566 and t table = 2.048, resulting in t count ≥ t table or 6.566 ≥ 2.048. with the conclusion that H0 is rejected and Ha is accepted, meaning that there is a significant difference in the use of the Type Card Sort learning strategy with the Expository learning strategy.